Productivity in New Zealand: the role of resource allocation among firms. Issue 1 (2nd January 2020) - Meehan, Lisa
ABSTRACT: This paper analyses the role of resource allocation in New Zealand's productivity performance by applying a three-factor revenue productivity measure of within-industry misallocation to firm-level data. It finds that if all market distortions were eliminated, total factor productivity could increase by more than a third. However, resource allocation has improved somewhat over the 2000s due to improvements in the manufacturing and service sectors, while allocation has worsened in the primary and utilities sectors. This paper is the first to use a three-factor decomposition method to examine which distortions have contributed to changes in allocative efficiency over time. These decompositions show that the worsening resource allocation in the primary and utilities sectors mainly reflects increased distortions in the allocation of capital. The results also suggest that many small firms are larger than their optimal size given their low productivity levels, which is consistent with previous research showing a comparatively poor 'up-or-out' dynamic among New Zealand firms.